INCIDENCE OF OPEN REDUCTION VERSUS CLOSED REDUCTION IN TREATING ZYGOMATICOMAXILLARY COMPLEX FRACTURES - AN INSTITUTIONAL BASED RETROSPECTIVE STUDY - .P, Rithanya; M., Sivakumar; .R, Subhashree (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Zygomaticomaxillary complex fractures (ZMC) are relatively common. They are also known as the tetrapod fractures. They are most commonly followed by the nasal bone fractures because of their prominent location. It complexly involves four bones, namely maxillary, temporal, orbital, and the greater wing of the sphenoid bone. At the same time, it is difficult to obtain perfect reduction and contour the facial structure postoperatively because of its complex involvement. Aim of the study: The aim of the present study was to analyse the incidence rate of open reduction versus the closed reduction in zygomaticomaxillary complex fractures. Thereby providing better treatment for better outcomes, including esthetics, restorations of anatomical form, occlusion, functions, and neurological defects. Materials and methods: Retrospective analysis of all the operational cases (open reduction and closed reduction) of zygomaticomaxillary complex fractures between June 2019 and March 2020 was retrieved among the overall data of 860000 patients visiting Saveetha Dental College. The data was entered in the Excel spreadsheets. And the collected data was analysed using SPSS software version 19. A chi-square test was done to evaluate the results. Results: Among the overall 25 cases reviewed, the male population (91.30%) had a higher prevalence of ZMC fractures. And the mean age group was between 20 and 40 years of age (56.52%). Between open and closed reductions in zygomaticomaxillary fracture treatments, open reduction (56.52%) had a higher prevalence compared to closed reduction (43.48%). In correlation between age, gender, and the treatment (open/closed reduction) in ZMC fractures. (p value > 0.05), which is statistically not significant. Conclusion: From the present small sampled retrospective study, open reduction with internal fixation in managing zygomaticomaxillary complex fractures has been dominating over closed reduction.